Statistical Approaches in GIS-Based Techniques for Sustainable Planning: Kayaçukuru Case - Aygun Erdogan (European Regional Science Association (ERSA), 2003)
The purpose of this study is to make both a summary and additional descriptive and inferential statistical analyses for a completed thesis on "Sustainable/Environment Friendly Development Planning of Fethiye-Kayaçukuru Using GIS-Based Techniques" (M.Sc. in the Graduate School of Geodetic and Geographic Information Technologies, Middle East Technical University, Supervisor: Assoc.Prof.Dr. Oğuz Işık, September 2000, 214 pages). The statistical analyses explained in this paper comprise a part of the whole GIS-based techniques developed for a case study about Fethiye-Kayaçukuru Plain to explore the contributions of such an approach. In this respect, first, the study area, spatial and non-spatial data and the way they are handled are introduced. Then, the performed statistical descriptive and predictive analyses/models and their interpretations in the developed "loose-coupled" "decision/planning support system" are mentioned. Finally, the concluding remarks of the study are discussed emphasising the contributions of this approach in the sustainable/environment friendly development planning and in particular for the Plain. Keywords: Sustainable/environment friendly development, decision/planning support system, non-spatial and spatial statistical analyses, statistical testing, modelling.
Keywords: 330